Comparative regenerative biology of spiny (Acomys cahirinus) and laboratory (Mus musculus) mouse skin. Issue 4 (29th April 2019) - Jiang, Ting‐Xin; Harn, Hans I‐Chen; Ou, Kuang‐Ling; Lei, Mingxing; Chuong, Cheng‐Ming
Abstract: Wound‐induced hair follicle neogenesis (WIHN) has been demonstrated in laboratory mice ( Mus musculus ) after large (>1.5 × 1.5 cm 2 ) full‐thickness wounds. WIHN occurs more robustly in African spiny mice ( Acomys cahirinus ), which undergo autotomy to escape predation. Yet, the non‐WIHN regenerative ability of the spiny mouse skin has not been explored. To understand the regenerative ability of the spiny mouse, we characterized skin features such as hair types, hair cycling, and the response to small and large wounds. We found that spiny mouse skin contains a large portion of adipose tissue. The spiny mouse hair bulge is larger and shows high expression of stem cell markers, K15 and CD34. All hair types cycle synchronously. To our surprise, the hair cycle is longer and less frequent than in laboratory mice. Newborn hair follicles in anagen are more mature than C57Bl/6 and demonstrate molecular features similar to C57Bl/6 adult hairs. The second hair cycling wave begins at week 4 and lasts for 5 weeks, then telogen lasts for 30 weeks. The third wave has a 6‐week anagen, and even longer telogen. After plucking, spiny mouse hairs regenerate in about 5 days, similar to that of C57Bl/6. After large full‐thickness excisional wounding, there is more de novo hair formation than C57Bl/6. Also, all hair types are present and pigmented, in contrast to the unpigmented zigzag hairs in C57Bl/6 WIHN. These findings shed new light on the regenerative biology of WIHN and may help us understand the control of skin repair vs regeneration.